β-Elemene promotes ferroptosis and reverses radioresistance in gastric cancer by inhibiting the OTUB1-GPX4 interaction - Jiancheng He; Jiancheng He; Jiancheng He; Ming Li; Ming Li; Ming Li; Jiapeng Bao; Jiapeng Bao; Jiapeng Bao; Yifeng Peng; Yifeng Peng; Yifeng Peng; et al. (Frontiers Media S.A., 2024)
Introductionβ-Elemene, derived from Curcuma zedoaria (Wenyujin), is clinically recognized for inducing apoptosis, inhibiting cell cycle progression, and reversing chemotherapy resistance in various cancers. However, its effects on radioresistant gastric cancer (GC) remain unclear.MethodsIn this study, radioresistant GC cell lines (MKN45/IR and AGS/IR) were established via multiple low-dose radiations. The impact of β-elemene on radiosensitivity was assessed using CCK-8 and clonogenic assays, with ferroptosis markers such as ROS, MDA, and Fe2+ levels measured. Additionally, the influence of β-elemene on GPX4 and its interaction with OTUB1 was examined through qRT-PCR, Western blot, immunofluorescence, co-immunoprecipitation, and in vivo studies.ResultsOur findings indicate that β-elemene reverses radioresistance in GC cells and significantly inhibits cell growth when combined with radiotherapy. β-Elemene treatment elevated ROS, MDA, and Fe2+ levels, enhancing ferroptosis, which was confirmed by Ferrostatin-1 and Deferoxamine inhibition studies. Mechanistic analysis revealed that β-elemene disrupts the OTUB1-GPX4 interaction, leading to increased GPX4 ubiquitination and degradation, thus promoting ferroptosis. In vivo studies further demonstrated that β-elemene combined with radiotherapy significantly suppressed tumor growth compared to radiotherapy alone.DiscussionThese results suggest that β-elemene effectively modulates radioresistance in GC by targeting the GPX4 pathway and inducing ferroptosis. This highlights its potential as a therapeutic adjunct in radiotherapy for resistant GC cases.